Предмет: Математика,
автор: sakhnoalina7
Решите (5-√13)+(5+√13)
Ответы
Автор ответа:
1
Ответ:
12
Пошаговое объяснение:
По формуле сокращенного умножения
а^2 - b^2 = (a-b)(a+b)
(5-√13)+(5+√13) = 5^2 - √13^2 = 25-13 = 12
Автор ответа:
1
Пошаговое объяснение:
ответ
connectshop290920:
спасибо
Похожие вопросы
Предмет: Русский язык,
автор: Kiri4ka1
Предмет: Русский язык,
автор: sabinka07041
Предмет: Русский язык,
автор: Jasminatalasbe
Предмет: Русский язык,
автор: LordNoName
Предмет: Физика,
автор: vitaliakovac